Beispiel Nr: 24
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 5 x +6 y =7\\ 4 x +6 y = 4 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} \\I \qquad 5 x +6 y =7\\ II \qquad 4 x +6 y = 4 \\ I \qquad 5 x +6 y =7 \qquad / \cdot4\\ II \qquad 4 x +6 y = 4 \qquad / \cdot\left(-5\right)\\ I \qquad 20 x +24 y =28\\ II \qquad -20 x -30 y = -20 \\ \text{I + II}\\ I \qquad 20 x -20 x+24 y -30 y =28 -20\\ -6 y = 8 \qquad /:\left(-6\right) \\ y = \frac{8}{-6} \\ y=-1\frac{1}{3} \\ \text{y in I}\\ I \qquad 5 x +6\cdot \left(-1\frac{1}{3}\right) =7 \\ 5 x -8 =7 \qquad / +8 \\ 5 x =7 +8 \\ 5 x =15 \qquad / :5 \\ x = \frac{15}{5} \\ x=3 \\ L=\{3/-1\frac{1}{3}\} \end{array} & \begin{array}{l} \\I \qquad 5 x +6 y =7\\ II \qquad 4 x +6 y = 4 \\ I \qquad 5 x +6 y =7 \qquad / \cdot1\\ II \qquad 4 x +6 y = 4 \qquad / \cdot\left(-1\right)\\ I \qquad 5 x +6 y =7\\ II \qquad -4 x -6 y = -4 \\ \text{I + II}\\ I \qquad 5 x -4 x+6 y -6 y =7 -4\\ 1 x = 3 \qquad /:1 \\ x = \frac{3}{1} \\ x=3 \\ \text{x in I}\\ I \qquad 5 \cdot 3 +6y =7 \\ 6 y +15 =7 \qquad / -15 \\ 6 y =7 -15 \\ 6 y =-8 \qquad / :6 \\ y = \frac{-8}{6} \\ y=-1\frac{1}{3} \\ L=\{3/-1\frac{1}{3}\} \end{array} \end{array} $